2007
DOI: 10.1021/ma062654j
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Layered Structure of Polymeric Micelles by SANS

Abstract: Small-angle neutron scattering (SANS), under shear using a Couette cell in radial and tangential scattering geometry, was performed to examine the structural evolution of the polymeric micellar macrolattice formed by concentrated aqueous solutions of triblock copolymerpoly(ethylene oxide)99−poly(propylene oxide)69−poly(ethylene oxide)99 (Pluronic F127)as a function of the shear rate. The micellar gel showed a shear thinning, i.e., a reduction of the resistance to shear, by forming a layered stacking of two-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
76
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 21 publications
5
76
0
Order By: Relevance
“…The maximum degree of order is observed when the shear stress reaches a plateau value during the large amplitude oscillatory shear cycle, whereas melting is maximized at the strain rate wave peaks. This structural evolution confirms the cyclic mechanism of sticking and sliding of 2D hexagonal close-packed layers [I. W. Hamley Formation of two-dimensional hexagonal close-packed (hcp) layers upon applying shear deformation to colloidal crystals has been described theoretically by Loose and Ackerson [1] and observed experimentally via small angle scattering measurements [2][3][4][5][6][7][8][9][10]. Under steady shear, the layered structure has a lower resistance to flow with respective shear thinning response.…”
supporting
confidence: 70%
See 2 more Smart Citations
“…The maximum degree of order is observed when the shear stress reaches a plateau value during the large amplitude oscillatory shear cycle, whereas melting is maximized at the strain rate wave peaks. This structural evolution confirms the cyclic mechanism of sticking and sliding of 2D hexagonal close-packed layers [I. W. Hamley Formation of two-dimensional hexagonal close-packed (hcp) layers upon applying shear deformation to colloidal crystals has been described theoretically by Loose and Ackerson [1] and observed experimentally via small angle scattering measurements [2][3][4][5][6][7][8][9][10]. Under steady shear, the layered structure has a lower resistance to flow with respective shear thinning response.…”
supporting
confidence: 70%
“…EAN is advantageous over water in that it has negligible vapor pressure; however, it must be dried and is hygroscopic. F127 is an amphiphilic copolymer that forms spherical micelles in water and in EAN [5,18,19]. Jiang et al reported the layered structure of a 20 wt% F127 aqueous solution induced by steady shear [5], which they related to the shear thinning behavior observed in a wide range of shear rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Micelle formation at room temperature was not observed in solutions of less hydrophobic polymers (Alexandridis, Holzwarth, & Hatton, 1994) but with an increase in temperature micelle formation occurs, which could be due to decreased solubility at higher temperatures. These interactions lead to structural arrangement of micelles into cubic quasicrystalline lattices with face-centered or body-centered cubic lattice arrangements (Jiang et al, 2007;Mortensen, Batsberg, & Hvidt, 2008). These polymers fall in the category of block copolymers as shown in Figure 1.4.…”
Section: Poly(ethylene Oxide)-poly(propylene Oxide)poly(ethylene Oxidmentioning
confidence: 99%
“…In-situ SANS investigations were performed using the radial and tangential neutron beam configurations. 60 The spherical micelles were seen to form layered macrolattice structures characterized by single-crystal type scattering (with bright diffraction spots). Transition from face-centered cubic structure at low shear rates to random layer stacking at high shear rates was observed.…”
Section: Polymer Micellesmentioning
confidence: 99%